quadratic equation.......
Attachments:
![](https://hi-static.z-dn.net/files/d48/40c43e4ddf84885be1f09d669e47a314.jpg)
Answers
Answered by
6
Heya!
--------
=====================================================
♦Quadratic Equation ♦
=====================================================
⭐Given that =>
==============
♦2 is a root of the Equation !
![= > let \: \alpha \: and \: \beta \: be \: the \: two \: roots = > let \: \alpha \: and \: \beta \: be \: the \: two \: roots](https://tex.z-dn.net/?f=+%3D++%26gt%3B+let+%5C%3A++%5Calpha+++%5C%3A+and+%5C%3A++%5Cbeta++%5C%3A+be+%5C%3A+the+%5C%3A+two+%5C%3A+roots)
We know that ,
![\alpha + \beta = 0(given) \\ \\ \alpha = 2 \\ \\ = > 2 + \beta = 0 \\ \\ = > \beta = - 2 \alpha + \beta = 0(given) \\ \\ \alpha = 2 \\ \\ = > 2 + \beta = 0 \\ \\ = > \beta = - 2](https://tex.z-dn.net/?f=+%5Calpha++%2B++%5Cbeta++%3D+0%28given%29+%5C%5C++%5C%5C++%5Calpha++%3D+2+%5C%5C++%5C%5C++%3D++%26gt%3B+2+%2B++%5Cbeta++%3D+0+%5C%5C++%5C%5C++%3D++%26gt%3B++%5Cbeta++%3D++-+2)
♦Now Sum of Roots = 0
♦Product of Roots = -4
⭐p (x) = x² -sx + p.............(1)
Put Values in (1)
P (x ) = x² - 0x - 4
=>> P ( x ) = x² - 4 =0
================
✔Option (b) is correct ✔
=======================================================
--------
=====================================================
♦Quadratic Equation ♦
=====================================================
⭐Given that =>
==============
♦2 is a root of the Equation !
We know that ,
♦Now Sum of Roots = 0
♦Product of Roots = -4
⭐p (x) = x² -sx + p.............(1)
Put Values in (1)
P (x ) = x² - 0x - 4
=>> P ( x ) = x² - 4 =0
================
✔Option (b) is correct ✔
=======================================================
guru8:
you got amazing skills
Answered by
2
given sum of roots (x+ y) = 0
let ,one root ,y = 2
sum of roots = x + y =0
x + 2 = 0
x = - 2 ,
product of roots ,
xy = -2 × 2= - 4
so the obtained quadratic polynomial
= X^2 - ( x + y ) X + xy
= X^2 - ( 0) X - 4
= X^2 - 4 = 0
hence, option (b) is the right answer.
●hope it helps ●
let ,one root ,y = 2
sum of roots = x + y =0
x + 2 = 0
x = - 2 ,
product of roots ,
xy = -2 × 2= - 4
so the obtained quadratic polynomial
= X^2 - ( x + y ) X + xy
= X^2 - ( 0) X - 4
= X^2 - 4 = 0
hence, option (b) is the right answer.
●hope it helps ●
Similar questions